2022
DOI: 10.1590/fst.103221
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification synthesis of high-yield biodiesel from black soldier fly larvae by using the combination of Lipase Eversa Transform 2.0 and Lipase SMG1

Abstract: The larvae of black soldier fly (BSFL) are rich in lipids, and in the current study, BSFL was used to produce biodiesel by enzymatic transesterification with methanol. Biodiesel obtained by free lipase-catalyzed transesterification is always with side-reactions. To address the limitation of free lipase, for the first time, Lipase SMG1 and Lipase Eversa Transform 2.0 were combined to use as catalysts at the same time. The effects of different reaction conditions on the yield of biodiesel were investigated, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
(36 reference statements)
0
16
0
2
Order By: Relevance
“…Os trabalhos selecionados têm métodos diferentes para a produção de biodiesel, como a transesterificação, solventes, catalisadores e entre outras formas (HE, 2022;TANG, 2022;NGUYEN, 2020). Estes métodos mencionados têm a função de tentar produzir o biodiesel com a melhor qualidade possível, assim com a utilização desses mecanismos químicos consegue-se precisar a extração dos lipídios, e dessa forma transformando em biodiesel.…”
Section: Resultsunclassified
“…Os trabalhos selecionados têm métodos diferentes para a produção de biodiesel, como a transesterificação, solventes, catalisadores e entre outras formas (HE, 2022;TANG, 2022;NGUYEN, 2020). Estes métodos mencionados têm a função de tentar produzir o biodiesel com a melhor qualidade possível, assim com a utilização desses mecanismos químicos consegue-se precisar a extração dos lipídios, e dessa forma transformando em biodiesel.…”
Section: Resultsunclassified
“…Through a process known as transesterification, which entails the reaction of triglycerides (fat/oil) with alcohol, leading to the formation of esters and glycerol it is possible to convert the fat/oil extracted from these insects into biodiesel. [ 9,10,20 ] A relevant study conducted by He et al. [ 10 ] explored the production of biodiesel from BSFL using enzymatic transesterification with lipase SMG1 and lipase eversa transform 2.0 as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10,20 ] A relevant study conducted by He et al. [ 10 ] explored the production of biodiesel from BSFL using enzymatic transesterification with lipase SMG1 and lipase eversa transform 2.0 as catalysts. The results of their investigation demonstrated that employing a combination of lipase SMG1 and lipase eversa Transform 2.0 as catalysts led to a significantly higher yield of biodiesel compared to the use of a single enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations